When x is equal to -1:
f(-1)=6(-1)-3
=-7-3
=-10
y=-10
When x is equal to 0:
f(0)=6(0)-3
=0-3
=-3
y=-3
When x is equal to 1:
f(1)=6(1)-3
=6-3
=3
y=3
When x is equal to 2:
f(2)=6(2)-3
=12-3
=9
y=9
Answer:
Step-by-step explanation:
The correct answer would actually be 15 because (-5) multiplied by -3 makes it positive 15.
Answer:
It's y-x= -4
Step-by-step explanation:
I drew the graph and figured out the points. Hope this helps.
Answer:
135
Step-by-step explanation:
1. 540/60=9
2.9×15=135
2,3,5! 1 is NOT a prime number!